Eksistensi Peningkatan Kualitas Sumber Daya Manusia Menuju Koperasi Sehat Pada Koperasi Di Kabupaten Kepulauan Meranti - Detri Karya; Efi Susanti; Hafidzah Nurjannah; Kamar Zaman (Yayasan Riset dan Pengembangan Intelektual, 2024)
Development of social welfare in Indonesia can be improved through the establishment of cooperatives, which is in accordance with the mandate of the state constitution. For cooperatives to be successful, professional and effective management is required, which includes the principles of good governance, transparency and accountability. This is important to ensure that all members have access to relevant and accurate information and are responsible for financial management and reporting. The application of these principles also aims to improve cooperative performance and build positive relationships with all stakeholders. Improvements are needed in managing human resources and conducting management to increase professionalism and performance. Although some cooperative principles are often overlooked, especially in terms of accountability, their emphasis on human resource development and good leadership can help overcome these obstacles and achieve shared goals. The success of cooperatives depends on the application of the principles of cooperation, participation, empowerment, openness and poverty, as well as continuous improvement in human resource management.